The Effect of Transformational Leadership, Self Efficacy and Self Learning toward Lecturers Job Performance at STAIN Curup Rejang Lebong Regency of Bengkulu Province (International Journal of Scientific Research and Management (IJSRM), 2018)
This research aims to analyze direct effect of transformational leadership, self efficacy and self learning toward lecturers Job performance at STAIN Curup. This research is newest research by using research model about lecturer’s performance which was surveyed from the effect of transformational leadership (indicators: effectiveness, productivity and usefulness), self efficacy factors (indicators: mobilize motivation, cognitive resource, job difficulty level and attitude selection), and self learning (indicators: self assesment, self improvment and self reinforcement). This research used quantitative approach with survey method and path analysis technique. Population was 96 civil servant lecturers. Findings of the research showed that there is a positive effect of transformational leadership toward lecturer’s job performance with value of 0.2390, positive effect self efficacy and lecturers job performance with value of 0.3040 and positive effect of self-learning torward lecturers job performance with value of 0.2720, there is also dirrect effect of transformational leadership toward self learning with value of 0.2740, self efficacy toward self learning with value of 0.4920, and transformational leadership toward self efficacy with value of 0.2670.